Cultural-Based Dispute Resolution in the Kankain Karkara Mananwir System of the Byak Community in Papua - Bruri Marwano Wutwensa; Nisrawanty Lembang (JUSTISI, 2026)
This study aims to examine the culturally based dispute resolution system known as Kankain Karkara, administered by the Mananwir customary institution within the Byak community in Biak, Papua, and to analyze its role in restoring social harmony amid the coexistence of formal and customary legal systems, including in disputes involving migrants. This study uses a legal anthropology approach through participant observation and in-depth interviews with customary authorities and community members, both indigenous residents and migrants. The analysis is grounded in the framework of legal pluralism and the concept of semi-autonomous social fields to examine the relationship between state law and customary law in dispute resolution practices. The novelty of this research lies in the finding that the Kankain Karkara system is not confined to homogeneous customary communities but operates as an inclusive and restorative mechanism capable of integrating migrants as subjects of dispute resolution through reconciliation processes based on local values. In addition, this study identifies the phenomenon of post-adjudication, in which disputes that have been formally decided by state courts continue to be processed through customary forums to achieve social certainty and the restoration of inter-family relations. Findings show that the Kankain Karkara system operates through a tiered and restorative mechanism involving two levels of customary authority: Mananwir Keret, which addresses intra-clan disputes based on reputational–ethical authority, and Mananwir MNU, which functions as a mediator for inter-community and cross-identity disputes through structural–genealogical authority. This study concludes that the coexistence of formal and customary justice systems Biak does not represent a jurisdictional conflict but rather a form of complementary functional differentiation, in which state courts provide procedural certainty, while Kankain Karkara delivers substantive justice through reconciliation and the restoration of social order.